ANALISIS PENGARUH PELAYANAN, SUKU BUNGA, DAN LOKASI TERHADAP KEPUASAN NASABAH PT.BPR NUR SEMESTA INDAH CABANG SEMBORO - Suharto, Akhmad; Winahyu, Pawestri; Nikmah, Rif'atun (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Customer satisfaction in the service sector is a customer's short-term emotional reaction to the performance of certain services, the level of customer satisfaction can occur after experiencing whether the services they expect are met or exceeded. If the customer feels disappointed, dissatisfied after receiving the service, it will cause problems for the service provider, if the customer feels happy and satisfied after receiving the service provided, it will lead to customer satisfaction. This research was conducted on customers of PT. BPR Nur Semesta Indah Semboro. This research was conducted to find out whether the less friendly and less fast service in serving transactions has an effect on customer satisfaction, whether the interest rate which is rather high compared to state-owned banks has an effect on customer satisfaction, whether the location of companies that enter villages far from the city center has an effect on satisfaction . This study aims to determine the effect of service on customer satisfaction, to determine the effect of interest rates on customer satisfaction, and to determine the effect of company location on customer satisfaction at PT. BPR Nur Semesta Indah Semboro Branch. Methods of data collection in this research using questionnaires, observation, and interviews. . The analysis technique used in this study is multiple linear regression with the help of the SPSS21 program. From the results of research that has been done, based on the results of the t test the service variable has a t calculated value of 3.490 with a significant value of 0.001, the data shows that service perception has a positive effect on customer satisfaction, the interest rate variable has a t calculated value of 7.334 with a significant value of 0.000, the data shows that the perception of interest rates has a positive effect on customer satisfaction, and the location variable, namely the t-count value of 5.293 with a significant value of 0.000, the data shows that the perception of location has a positive effect on customer satisfaction.